Legal Protection for Creditors Due to Problem Credit with Collateral Rights Guarantee - Arifardhani, Yoyo; Jum Anggriani; Silvia Dantyana (Inovasi Pratama Internasional. Ltd, 2025)
Legal consequences of the implementation of the Power of Attorney to Charge Mortgage Rights in the implementation of the Sale and Purchase Agreement by a Notary based on the main agreement, namely the Credit Agreement in Banking which is not followed by the making of a Deed of Granting Mortgage Rights and analyzing legal protection for creditors in credit agreements with the execution of mortgage guarantees if the debtor is in default for settlement due to problematic credit. Based on Article 8 of Law No. 10 of 1998 concerning Amendments to Law No. 7 of 1992 concerning Banking in providing credit, banks apply the principle of